Peningkatan Kompetensi Guru Sekolah Dasar Melalui Pelatihan Media Pembelajaran Berbasis Augmented Reality dan Video Digital - Ahmad Heru Mujianto; Hadi Sucipto; Rahma Ramadhani (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
Augmented Reality (AR) technology is a technology that helps visualize objects in a more real form (3 dimensions). The concept of AR technology is not only applied to games but can also be applied to the field of education to provide understanding and learning motivation for students. The problem that occurs in elementary school students is the lack of interest and motivation to learn mathematics, especially about geometric figures, which has an impact on reducing the final mathematics score. It is hoped that the implementation of training in making AR and learning videos can be used by teachers to provide learning innovation and increase student motivation. Community service activities are carried out in the Megaluh District elementary school teacher working group, totaling 17 elementary schools. The final results of this PKM activity received a positive response from the training participants, with a satisfaction level of above 70%, and they hope that activities like this can be carried out regularly to provide knowledge updates in the field of technology for education.